Heparin Attenuates Histone-Mediated Cytotoxicity in Septic Acute Kidney Injury - Wang, Ziyi; Wang, Lijun; Cao, Chao; Jin, Heng; Zhang, Yan; Liu, Yancun; Gao, Yulei; Liang, Xue; Li, Guangping; Shou, Songtao (Frontiers in Medicine, 2020)
Histones are considered potential risk factors that contribute to the development of septic acute kidney injury (SAKI) by inducing apoptosis and inflammation. This study aimed to explore the protective effects of heparin on septic acute kidney injury through the neutralization of extracellular histones (EH) and to uncover the underlying mechanism. C57BL mice (12 each) were randomly divided into the sham group, sepsis group (established by cecal ligation and puncture operation), and the heparin intervention group. Mice in the heparin intervention group received subcutaneous injection of unfractionated heparin (0.03 IU/g) 4 h after cecal ligation and puncture operation (CLP). Six hours after the operation, nine mice from each group were sacrificed by removal of the eyeballs to harvest blood samples; the upper half of the right kidney was used as the study sample. Mice renal tubular epithelial cells cultivated in 6-well plates were equally divided into three groups, namely the control, histone stimulation, and heparin intervention groups. Cells in the histone stimulation group were treated with histone (40 U); while cells in the heparin intervention group were treated with histone and unfractionated heparin (4 U/mL) simultaneously. Mice in the heparin intervention group showed decreased levels of EH4, neutrophil gelatinase-associated lipocalin (NAGL), kidney injury molecule-1 (KIM-1), tumor necrosis factor-α (TNF-α) and interleukin (IL)-6 in the blood serum, longer average survival rate at 72 h, significantly decreased kidney tissue edema, a clearer glomerular structure coupled with decreased protein and mRNA expression levels of kidney apoptosis-related proteins (cleaved-Caspase-3/Caspase-3 and Bax/Bcl-2) compared with those in the sepsis group at 6 hours after CLP (P<0.05). Meanwhile, cells in the heparin intervention group exhibited lower expression levels of serum EH4 and inflammatory cytokines, a lower apoptosis rate, and decreased expression of apoptosis-related proteins both at protein and mRNA levels than those in the histone stimulated group at 6 hours after stimulation (P<0.05). Heparin may alleviate apoptosis and inflammation through the neutralization of histones, thus playing a protective role against septic acute kidney injury.